Chemistry directs the conservation of paper cultural relics - Zhang, Xu; Yan, Yueer; Yao, Jingjing; Jin, Shutong; Tang, Yi (Polymer degradation and stability, 2023)
•Chemical principles are used to direct the preservation and conservation of paper cultural relics.•The mechanisms of acidic, alkaline and oxidative degradation of cellulose, hemicellulose and lignin in paper are summarized.•The intrinsic and extrinsic factors affecting the degradation process of paper are addressed.•The advantages and disadvantages of remedial and preventive conservation methods for paper relics are discussed. Paper cultural relics, with the great historic and artistic value, experience aging and degradation during their long-term preservation. The degradation of paper involves various chemical reactions with complicated mechanisms due to the multiple components of paper itself and the complex factors that promote paper aging process. Therefore, it is of great importance to deeply understand the chemical essence and scientific principle of paper degradation, so as to propose the effective conservation methods for paper relics. This review summarized the chemical mechanisms of acidic, alkaline and oxidative degradation of cellulose, hemicellulose and lignin in paper, and discussed the intrinsic and extrinsic factors that affect paper degradation systematically. Moreover, the interaction among the three types of degradation routes was analyzed for the first time, and the evolution of kinetic models for paper degradation was introduced to evaluate the durability and expected lifetime of paper. On this basis, the advantages and disadvantages of remedial and preventive conservation methods for paper relics are summarized, and the fundamental scientific principles was prospected to guide the further development of paper conservation methods.